2014
DOI: 10.1097/mbp.0000000000000022
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of resistance exercise does not modify cardiovascular responses during daily activities in patients with peripheral artery disease

Abstract: Objective To analyze the post-effects of a single bout of resistance exercise on cardiovascular parameters in patients with peripheral artery disease (PAD). Design Randomized cross-over. Methods Seventeen PAD patients performed two experimental sessions: control (C) and resistance exercise (R). Both sessions were identical (8 exercises, 3 × 10 reps), except that R session was performed with intensity between 5–7 in the OMNI-RES scale and the C session was performed without any load. Systolic blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
(55 reference statements)
3
19
0
2
Order By: Relevance
“…Hence, circadian variation probably explains the increase in BP from preintervention values in the control condition, as although standing produces an important orthostatic stress, hemodynamic measurements were taken at least 45 min after the patients had reverted back to the supine position (same for the WE condition). This is consistent with previous studies undertaken at a similar time of the day in this patient group (9,31). It is also interesting to note that a blunted or absent PEH response in comparison with preexercise values has been reported previously in healthy individuals after morning exercise (20).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, circadian variation probably explains the increase in BP from preintervention values in the control condition, as although standing produces an important orthostatic stress, hemodynamic measurements were taken at least 45 min after the patients had reverted back to the supine position (same for the WE condition). This is consistent with previous studies undertaken at a similar time of the day in this patient group (9,31). It is also interesting to note that a blunted or absent PEH response in comparison with preexercise values has been reported previously in healthy individuals after morning exercise (20).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, baseline values of arterial blood flow, resistance and arterial stiffness were within the limits described in previous studies involving PAD patients [10,45]. The increases in systolic BP observed after the control session have also been observed in other studies in normotensive and hypertensive subjects [27,33,38], as well as in PAD patients with intermittent claudication [10,37], and have been explained by circadian variation in BP during the morning [19]. On the other hand, after REx we observed the presence of a hypotensive effect in systolic (greatest decrease: − 10 mmHg), diastolic (greatest decrease: − 7 mmHg) and mean (greatest decrease: − 7 mmHg) BP.…”
supporting
confidence: 86%
“…We previously showed that after a single session of REx, there is a transient decrease in blood pressure (BP) that is maintained for up to 60 min [11,37], which could be considered potentially clinically relevant. However, the mechanisms underlying this response were not studied.…”
mentioning
confidence: 99%
“…After this, patients performed five-two-minute sets of walking at the previously determined speed. The exercise sessions were designed to have approximately the same duration (50 min), and the intensity of these sessions were established based on previous studies that prescribed walking (Cucato et al, 2013) and resistance exercise (Rodrigues et al, 2014) for these patients. After performing all the scheduled exercises for a session, the patients returned to the laboratory where they rested in the supine position for 40 min.…”
Section: Experimental Sessionsmentioning
confidence: 99%